Lessons from the COVID-19 pandemic: Insights into effective training strategies for physical development in football - Anderson, L.; Flannigan, C.; Polychronopoulos, P.; MacKenzie, R.; Drust, B.; Milsom, J. (International Journal of Sports Science & Coaching, 2023)
Professional soccer players typically perform regular training sessions and match play for most of the yearly macrocycle with limited time focused on solely developing physical development. The COVID-19 outbreak in 2020 caused mass disruption to professional soccer but provided an opportunity for an alternative approach to training in attempt to develop professional soccer players physical fitness levels. In a non-randomised and non-controlled study, we aimed to assess the effectiveness of a 13-week remote based physical training programme on physical fitness levels in elite professional soccer players. Twenty professional soccer players undertook body composition assessments, a countermovement jump (CMJ) test, eccentric hamstring strength test and a submaximal 30-15 intermittent fitness test (IFT) pre- and post-remote based training programme. Body mass (79.3 ± 6.7 vs. 80.0 ± 7.3 kg), skinfold thickness (54.1 ± 14.8 vs. 56.7 ± 15.2 mm), maximum CMJ height (38.4 ± 3.4 vs. 40.9 ± 4.1 cm), eccentric hamstring strength (1035 ± 158 vs. 1009 ± 140 n) and percentage max heart rate reached in submaximal 30-15 IFT (81.3 ± 5.2 vs. 82.3 ± 7.3%) were maintained (all P > 0.05) from pre- to post training programme, respectively. Although team-based soccer specific training load was removed, and the training programmes prescribed had an increased physical focus, fitness levels were maintained. This suggests that alternative modes of training can potentially be used in instances where team-based soccer specific training load isn`t required or is unavailable, without negatively impacting physical development.